Financial Development, Commercial Development, and Economic Growth in the Selected Emerging and the Middle Eastern Countries - Agheli, Lotfali; Hadian, Golnaz (International Journal of Economics and Financial Issues, 2017)
This study investigates panel causality relationships among financial development, commercial development and economic growth using bootstrap method in selected emerging and developing countries during 1980-2013. In this study, simultaneous equations, seemingly unrelated regression, Wald Test and Bootstrap critical tests are used to determine causality relationship among variables under study. Our findings indicate the difference of causality across countries and among different variables, so that in some countries, financial development has led to economic growth and in other countries, this has not happened because of lack of deep financial sector. However, in most countries, commercial development has led to improvement of economic growth. Moreover, the results imply difference in direction of causality from economic growth to both financial and commercial development. Keywords: Oil-dependent countries, emerging markets, panel causality JEL Classifications: C23, G32, P45